At the source of Greek rationalism - Dębiński, Bogdan (Folia Philosophica, 2000)
The present study is an attempt to show the connection that takes place between a specific type of philosophising and the thinker’s attitude towards the world. The author claims that the method of philosophising depends in every case on the specific attitude towards the world that the philosopher assumes. This claim is being substantiated in the context of a dispute over the problem of the sources of Greek philosophy. The attitude of Greek philosophers is shown as a condition of the rise of the specific form of Greek rationality which produced the extraordinary phenomenon of Greek culture and philosophy.